Dune - Herbert, Frank, 1920-1986 (New York : ACE, 2019)
In a far future interstellar empire, young noble Paul Atreides travels to the desert planet Arrakis, where he becomes embroiled in political conflict, ecological struggle, and a destiny that will change the universe.
Keywords: Science fiction; Interplanetary voyages -- Fiction; Political fiction